Učinki vadbenih programov Specialne olimpijade na telesno zdravje odraslih ljudi z intelektualno in razvojno motnjo - Kovačič, Tine (Kakovostna starost, 2019)
A modern society faces the challenge of providing vulnerable groups of adults with intellectual disabilities in the aging process with appropriate support in improving physical health and satisfaction with health and an active lifestyle. In the study we used the integration of a quantitative (randomized clinical study) and a qualitative (phenomenological study) research methodology in order to study the short-term effectiveness of the three different Special Olympics (SO) programs of physical activity on physical health and satisfaction with health and to qualitatively study the improvement in this case in athletes with intellectual disability. There were 150 athletes with intellectual disability who were classified into two study groups and one control group according to the principles of stratified randomization. Based on the analysis of the results of the domains physical health and satisfaction with health, we found that athletes in the Fun Fitness Plus and Wellness group achieved a statistically significant improvement in two domains (p <0.001) compared to athletes in the control group.
Keywords: osebe z intelektualno motnjo; osebe z razvojno motnjo; Specialna olimpijada; športniki; telesno zdravje; zadovoljstvo z zdravjem